Influence of ground basalt application on growth and nutrient status of Hevea brasiliensis (RRIM 3001) - Abdul Rahman, Nurul Afifah (2015)
Rubber (Hevea brasiliensis) belongs to the family of Euphorbiaceae. Though many research had been done pertaining to growth of rubber and nutrition, however in Malaysia there is no information on application of basalt to rubber. Thus, the purpose of this experiment is to determine the influence of ground basalt application on growth and nutrient status of Hevea brasiliensis (RRIM 3001). The new finding will be useful to rubber plantation industry to improve the nutrient availability, reduce cost of fertilizer and ability to face the problem of acidic soil. The experiment was conducted at Field 2, UPM. The treatments consist of five different treatments 0 g (control), 40 g, 80 g, 160 g and 240 g of basalt application and Christmas Island Rock Phosphate (CIRP) 25 g per polybag. Basalt was sieved using 0.1 mm siever to increase the surface area to fasten the process of reaction. Parameters on girth, height and chlorophyll content were collected every month. Other parameters including dry weight of root, leaves, stem, total dry weight of plant and nutrients content N, P, K, and Mg of plant tissues, were measured after 6 month. Soil chemical properties was analysed after 6 month of the experiment. Data was analysed using Analysis of Variance (ANOVA) and Statistical Analysis System (SAS). Least Significance Different (LSD) was used to determine the significant different between treatment means. From this study, plant that was treated with basalt shows the highest vegetative growth, soil nutrients content, fresh and dry weight. For height and girth T5 (201.11 cm and 1.4 cm) was significantly higher than T1 (122.66 cm and 1.1 cm). Fresh weights, dry weights of each part of plant leaf, stem, and root also highest in T5 and lowest in T1. For fresh weight, highest rate of basalt application, 240 g (T5) was higher significantly compared to non-applied basalt with value 562.6 g and 386.61 g respectively. Application of basalt seems no significant effect on leaf nutrient content. However, soil chemical properties such as pH, P, K, Ca, Mg, and K were increased with increasing rate of basalt applied. In conclusion, the result shows that ground basalt application enhance the growth performance of Hevea brasiliensis RRIM 3001 and increase nutrient status in soil.